2018
DOI: 10.1016/j.parkreldis.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thinning correlates of changes in visuospatial and visuoperceptual performance in Parkinson's disease: A 4-year follow-up

Abstract: In this study, we establish the neuroanatomical substrate of progressive changes in VS/VP performance in PD patients with and without MCI. In agreement with cross-sectional data, VS/VP changes over time are related to cortical thinning in posterior regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 35 publications
1
35
2
Order By: Relevance
“…29 According to our findings in PD-CNtoMCI, several cross-sectional MRI studies established a link between atrophy of posterior regions (mainly involving the parietal lobe) and cognitive impairment in PD patients, 30,31 and previous longitudinal studies assessing the conversion from normal cognition to MCI in PD patients showed greater progressive cortical thinning in parieto-temporooccipital regions. 5,32 The presence of early and progressive cortical abnormalities involving posterior areas has been recently demonstrated in early-diagnosed PD patients in association with reduced striatal dopamine transporter uptake. 33 Thus, these abnormalities, together with their association with lower cognitive performance of patients over time, were interpreted as an early indicator of dopaminergic depletion and a marker of neurodegenerative processes.…”
Section: Discussionmentioning
confidence: 99%
“…29 According to our findings in PD-CNtoMCI, several cross-sectional MRI studies established a link between atrophy of posterior regions (mainly involving the parietal lobe) and cognitive impairment in PD patients, 30,31 and previous longitudinal studies assessing the conversion from normal cognition to MCI in PD patients showed greater progressive cortical thinning in parieto-temporooccipital regions. 5,32 The presence of early and progressive cortical abnormalities involving posterior areas has been recently demonstrated in early-diagnosed PD patients in association with reduced striatal dopamine transporter uptake. 33 Thus, these abnormalities, together with their association with lower cognitive performance of patients over time, were interpreted as an early indicator of dopaminergic depletion and a marker of neurodegenerative processes.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that when assessing specifically VS/VP functions in PD, structural substrates encompass cortical thinning in lateral temporoparietal regions ( Garcia-Diaz et al, 2018a , Garcia-Diaz et al, 2014 ). Moreover, as PD progresses, VS/VP impairment is accompanied by bilateral posterior degeneration ( Garcia-Diaz et al, 2018b ). Although further longitudinal data with larger samples are needed to confirm our results, the decline in VS/VP performance might help to identify those patients presenting progressive neurodegeneration in posterior cortices.…”
Section: Discussionmentioning
confidence: 99%
“…It may not be fully interpreted by the spread of β-amyloid pathology alone [18•], but future studies that combine amyloid/tau PET and sMRI are warranted to shed further light on this assumption. Future studies should also explore how cholinergic neuron losses in the nucleus basalis of Meynert and other cholinergic structures of the basal forebrain impact the SPARE-AD pattern of atrophy in PD and the progression of memory and visuospatial deficits in PD [73]. Further studies exploring the effect of atrophy on distinct hippocampal subfields are also awaited.…”
Section: Discussionmentioning
confidence: 99%